The anti-avoidance response to professionals incorporating companies in Singapore - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2020)
The issue of whether the incorporating of companies by professionals in Singapore constitutes tax avoidance has attracted considerable attention. The recent case of GCL v. CIT provides some guidance in this area. It reaffirms the general two-part test in CIT v. AQQ, requiring one to first apply the objective predication principle before moving on to consider the subjective bona fides commercial reason exception. It establishes that the mere fact that a professional incorporated a company through which to practise would not be sufficient to constitute tax avoidance, since such an arrangement is common and widely used, with established commercial benefits. However, the salary paid to a professional is subject to scrutiny and cannot be artificially reduced. Doing so may constitute tax avoidance and/or attract an ‘arm’s length’ adjustment under section 34D of the ITA. It also establishes that the ‘personal exertion principle’ has no basis in Singapore.